Agricultural subsidies and international trade: what is the implication on world and Brazilian exports? - Viana Martins, Michelle Márcia; Cechin, Alicia; Queen Almeida Bispo, Scarlett; de Araújo Pedrosa, Fernanda; Braga Nonnenberg, Marcelo José (Estudios económicos, 2024)
The aim of the study was to estimate the effects of agricultural subsidies from third countries on world and Brazilian agricultural exports. The gravitational model was applied to the agricultural flows aggregated and disaggregated by products, in the years 2004 to 2019. The results indicate that producer support negatively affects Brazilian and world exports from the perspective of aggregate agribusiness exports. Moreover, a more detailed analysis at the sectoral level revealed that the product-specific subsidy has a positive relationship with Brazilian exports of soy, corn, beef and pork, and a negative one with sugar shipments through Brazil.